2013
DOI: 10.1111/liv.12278
|View full text |Cite
|
Sign up to set email alerts
|

Drug‐induced hepatotoxicity: incidence of abnormal liver function tests consistent with volatile anaesthetic hepatitis in trauma patients

Abstract: Volatile anaesthetic drug-induced liver injury in adult trauma patients may be significantly more common than previously noted. This study suggests that about a quarter of patients with volatile anaesthetic drug-induced liver injury develop significant liver injury. Further prospective studies are required to define risk factors and clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 23 publications
5
20
1
Order By: Relevance
“…These inconsistent results could be accounted for by patient severity and referral patterns. Patients reported by Lin et al study had less severe disease whereas several patients reported in the Walsh et al study had hepatic injury and failure.…”
Section: Diagnostic Criteriamentioning
confidence: 82%
See 1 more Smart Citation
“…These inconsistent results could be accounted for by patient severity and referral patterns. Patients reported by Lin et al study had less severe disease whereas several patients reported in the Walsh et al study had hepatic injury and failure.…”
Section: Diagnostic Criteriamentioning
confidence: 82%
“…There is an inconsistent relationship between the severity of skin injury and liver; Lin et al found no significant relationship between skin histopathological findings and liver injury, whereas Walsh et al from Kings College Hospital found patients with DRESS presenting with an atypical erythema multiforme (EM)‐like eruption (purpura and atypical targets) to be associated with severe hepatic involvement such as significantly marked elevation of serum aminotransferases (AST 2758 IU/L) compared with other types of skin pathology (AST 292; P = 0.01). Further, two out of eight patients with EM‐like DRESS died in contrast to one mortality out of 19 cases in the non‐EM‐like DRESS cohort.…”
Section: Diagnostic Criteriamentioning
confidence: 99%
“…Drug‐induced liver injury, or drug‐related hepatotoxicity, is injury to the liver due to exposure to a drug, as demonstrated by impaired liver function tests . Volatile anaesthetics are commonly used inhaled halogenated agents that are a recognised cause of drug‐induced liver injury . Volatile anaesthetic drug‐induced liver injury (VA‐DILI) typically causes a rise in the alanine transaminase (ALT) 2 to 14 days post‐operatively, and can manifest as a spectrum of disease, from asymptomatic derangement in liver biochemistry, to acute severe hepatitis, and rarely, fatal hepatic necrosis …”
Section: Introductionmentioning
confidence: 99%
“…Volatile anaesthetics are primarily metabolised by the cytochrome p450 enzyme, CYP2E1, which generates intermediates that can covalently bind to native cellular components, creating trifluoroacetylated lipid and protein adducts (TFA) . Immune‐mediated drug‐induced liver injury has been demonstrated in patients following modern volatile anaesthetics, but is less common than with halothane or enflurane …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation